2013
DOI: 10.5858/arpa.2013-0179-oa
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Large Cell Carcinoma Lacking Squamous Differentiation Is Clinicopathologically Indistinguishable From Solid-Subtype Adenocarcinoma

Abstract: Context.-Pulmonary large cell carcinoma (LCC) includes tumors not readily diagnosed as adenocarcinoma (ADC) or squamous cell carcinoma on morphologic grounds, without regard to immunophenotype, according to the World Health Organization (WHO). This ambiguous designation may cause confusion over selection of mutation testing and directed therapies. Several groups have proposed the use of immunohistochemistry (IHC) to recategorize LCC as ADC or squamous cell carcinoma; however, it remains unclear if strictly def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…1 Hirsch et al 4 demonstrated major heterogeneity by light microscopy in 13% of 200 consecutive lung cancers. 26,27 It is noteworthy that no histologic heterogeneity was recorded in biopsies, suggesting that the finding of histologic heterogeneity is more probable if large areas of tumor are available. Cell differentiation at electron microscopy is based on recognition of ultrastructural features on tiny pieces of tumor tissue, and mucin stains and primordial polyclonal antibodies are less specific than novel markers.…”
Section: Discussionmentioning
confidence: 99%
“…1 Hirsch et al 4 demonstrated major heterogeneity by light microscopy in 13% of 200 consecutive lung cancers. 26,27 It is noteworthy that no histologic heterogeneity was recorded in biopsies, suggesting that the finding of histologic heterogeneity is more probable if large areas of tumor are available. Cell differentiation at electron microscopy is based on recognition of ultrastructural features on tiny pieces of tumor tissue, and mucin stains and primordial polyclonal antibodies are less specific than novel markers.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies used for whole tissue sections included TTF-1 (8G7G3/1), napsin A (polyclonal), and CK5/6 (D5/16B4), all obtained from Roche Ventana (Tucson, Arizona), and were prediluted. The antibody for p40 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) was diluted to 1:3000 and was obtained from EMB Millipore (Billerica, Massachusetts). Immunostaining of whole tissue sections was performed with an automated stainer (BenchMark Ultra; Roche Ventana) and primary antibody incubation times ranging from 20 to 24 minutes.…”
Section: Reclassification By 2015 Who Criteriamentioning
confidence: 99%
“…The presence of EGFR mutations in these latter 2 entities likely reflects miscategorization of solid subtype ACA, in the case of large cell carcinoma, and possibly undersampling of an adenosquamous carcinoma, in the case of squamous cell carcinomas. [22][23][24] Most large studies 22,25 suggest that EGFR mutations virtually never occur in tumors lacking at least some ACA features. The predictive value of lung cancer subtyping for the presence of an underlying EGFR mutation has driven into relative obsolescence the term non-small cell lung carcinoma and, in fact, current recommendations generally discourage use of this term unless a tumor eludes classification despite histologic and immunophenotypic evaluation.…”
Section: -16mentioning
confidence: 99%
“…Among ACA with solidsubtype histology, the frequency of KRAS mutation is 40%. 23 The most common KRAS alteration in current and former smokers is a codon 12 G.T transversion mutation leading to p.Gly12Cys; transversions reflect the typical DNA-level alterations induced by tobacco carcinogens.…”
Section: Kras Mutationsmentioning
confidence: 99%